Uji Aktivitas Antibakteri Propionibacterium Acne ATCC 6919 Ekstrak Etanol Daun Si Kejut (Mimosa Pudica L) - Anna Fitriawati; Annie Rahmatillah; Nurul Agustiningrum (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Vulgaris acne is a chronic inflammatory condition commonly experienced by adolescents and young adults, with a prevalence reaching up to 85%. Propionibacterium acnes plays a significant role in the inflammatory process of acne, which is influenced by sebum production, hyperkeratinization, and the inflammatory immune response. Acne treatment often involves antibiotics, but resistance to antibiotics such as erythromycin and clindamycin has increased, creating serious challenges in dermatology. Therefore, the development of non-antibiotic therapies for acne is crucial. One promising alternative is the extract of Mimosa pudica L., also known as the sensitive plant, which is recognized for its antimicrobial activity. The extract of Mimosa pudica L. leaves has been shown to inhibit the growth of various pathogenic bacteria and has potential anti-inflammatory effects based on in silico studies, opening up significant opportunities for the development of plant-based treatments for acne and other inflammatory diseases. This study aims to evaluate the effectiveness of ethanol extract of Mimosa pudica L. leaves in inhibiting the growth of Propionibacterium acnes ATCC 6919. The results of the study show that the 30% ethanol extract can inhibit bacterial growth with an inhibition zone diameter of 11.537 mm, indicating the potential of this extract as a safer and more effective alternative treatment for acne.